Edukasi Literasi Keuangan bagi Remaja dalam Mengelola Uang Saku Pada Siswa SMA Negeri 3 Medan - Rolita C. Purba; Fransiska Tiurma Damanik; Saudaranta Tarigan; Ida Mariani Pasaribu (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
Wise financial management from adolescence is an important skill that needs to be instilled early. However, low levels of financial literacy among students often make it difficult for them to manage their pocket money effectively. This community service activity aims to provide financial literacy education to students of SMA Negeri 3 Medan to improve their understanding and skills in managing their pocket money wisely and responsibly. The activity implementation methods included interactive counseling, group discussions, and simple financial planning simulations. The results of the activity showed an increase in students' understanding of basic financial literacy concepts, such as the importance of saving, budgeting, and distinguishing between needs and wants. Furthermore, students also showed high enthusiasm in participating in the activity and were able to independently develop personal financial plans. This education is expected to provide initial provisions for adolescents in developing healthy financial habits and encourage the creation of a more financially literate young generation